Blowout dynamics and plasma-assisted stabilization of premixed swirl flames under fuel pulsations - Jinguo Sun; Hu Wu; Yong Tang; Chengdong Kong; Shuiqing Li (Applications in Energy and Combustion Science, 2023)
The present work investigates blowout dynamics of premixed swirl flames under low-frequency high-amplitude flow pulsations from the fuel feedline, and applies microsecond repetitively pulsed discharges with extremely-low power consumption to precisely control the stability of pulsating flames. First, both positive and negative fuel pulsations deteriorate the flame stability, causing much-narrowed lean blowout regimes. The fuel pulsation causes the flame to remain at the fuel-lean condition for a long period of time, which is considered to be the main cause of flame blowout. The flame response can be further explained by the convection process of the equivalence ratio oscillation. Secondly, the microsecond pulsed discharge with the same repetition rate as the fuel pulsation is used to alter the lean blowout via thermal, kinetic, and hydrodynamics effects. More importantly, the time delay between the discharge pulse and the fuel pulsation determines whether the plasma has an enhancement effect or not. It is found that the discharge prior to the convection of the equivalence ratio pulsation reaches the optimal effectiveness for flame stabilization, extending the blowout limit by approximately 10%. Finally, the lean blowout limit can be continuously extended with the increasing discharge repetition rate until saturation.